Automatic Verification of Strongly Dynamic Software Systems - Dor, Nurit; Field, John; Gopan, Denis; Lev-Ami, Tal; Loginov, Alexey; Manevich, Roman; Ramalingam, G.; Reps, Thomas; Rinetzky, Noam; Sagiv, Mooly; Wilhelm, Reinhard; Yahav, Eran; et al. (Working Conference on Verified Software: Theories, Tools, and Experiments, 2005)
Strongly dynamic software systems are difficult to verify. By strongly dynamic, we mean that the actors in such systems change dynamically, that the resources used by such systems are dynamically allocated and deallocated, and that for both sets, no bounds are statically known. In this position paper, we describe the progress we have made in automated verification of strongly dynamic systems using abstract interpretation with three-valued logical structures. We then enumerate a number of challenges that must be tackled in order for such techniques to be widely adopted.